The ecology of the Galapagos - Russell, George H.; Nolan, Mary Lee; Soare, Thomas F.
The complex interactions of wildlife in the unique environment of the Galapagos Islands provide excellent case studies of the principles of ecology. The learning objectives of this programme : 1) Students will learn about the unique kinds of life that are found on the Galapagos Islands. 2) Students will learn where the Galapagos Islands are located. 3) An explanation of how the islands were formed will be given.